2020
DOI: 10.14202/vetworld.2020.570-578
|View full text |Cite
|
Sign up to set email alerts
|

Univariate associations between housing, management, and facility design factors and the prevalence of lameness lesions in fourteen small-scale dairy farms in Northeastern Algeria

Abstract: Background and Aim: This cross-sectional study aimed to analyze the associations between different types of housing, management, and facilities on the prevalence of lame, causing lesions in smallholder dairy farms in Algeria. Materials and Methods: The on-site investigation took place between December 2012 and May 2015. All cows were locomotion scored on a four-point scale, and foot lesions causing lame were diagnosed and recorded. Factors related to the farm and the cows' conditions were also assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Rajnbar et al [ 6 ] reported 18.9% (range 5% to 44.5%); in grazed dairy cattle, the prevalence is from 8 to 31% [ 34 ]. The study conducted by Dendani-Chadi et al [ 36 ] reported that the prevalence of lame cows was significantly associated with pasture, in non-grazing cows (35.4%), in partially grazing (16.4%), and grazing throughout the year (1.3%). Another study estimated that a total of 75% of cows in Europe are affected by hoof disorders [ 9 ].…”
Section: Prevalence Of Lamenessmentioning
confidence: 99%
See 4 more Smart Citations
“…Rajnbar et al [ 6 ] reported 18.9% (range 5% to 44.5%); in grazed dairy cattle, the prevalence is from 8 to 31% [ 34 ]. The study conducted by Dendani-Chadi et al [ 36 ] reported that the prevalence of lame cows was significantly associated with pasture, in non-grazing cows (35.4%), in partially grazing (16.4%), and grazing throughout the year (1.3%). Another study estimated that a total of 75% of cows in Europe are affected by hoof disorders [ 9 ].…”
Section: Prevalence Of Lamenessmentioning
confidence: 99%
“…It is mainly at the forefront, due to the increasing prevalence and because no other common dairy disease is associated with such visible symptoms of pain [ 9 , 27 , 60 , 64 ], which may be of a long-term nature. Thus, in addition to adverse effects on production, lameness is associated with pain [ 6 , 11 , 22 , 25 , 26 , 31 , 32 , 36 , 40 , 46 , 55 , 60 , 65 , 66 , 67 ] and anxiety [ 60 ]. In this case, the dairy cow cannot exhibit natural behavior [ 6 , 40 , 55 , 63 , 68 ].…”
Section: Factors Influencing the Occurrence Of Lamenessmentioning
confidence: 99%
See 3 more Smart Citations